Faculty’s perception of their role as a tutor during Problem-Based Learning activity in undergraduate medical education - Isharyah Sunarno; Budu Mannyu; Suryani As’ad; Sri Asriyani; Irawan Yusuf; Rina Masadah; Agussalim Bukhari (The Asia Pacific Scholar, 2024)
Introduction: The study aimed to ascertain how the faculty at the Faculty of Medicine, Hasanuddin University perceived their role as a tutor during a problem-based learning activity during the academic phase of medical education, based on the length of time they acted as a tutor. Methods: This was prospective observational research with an explanatory sequential mixed-method design, which was performed at the Undergraduate Medical Study Program, Faculty of Medicine, Hasanuddin University, from January 2023 until May 2023. Research subjects were divided into two groups: a) the Novice group and b) the Expert group. Quantitative data were collected by giving a questionnaire containing six categories with 35 questions and distributed by Google form. An independent t-test was used to compare the faculty’s perception, with a p-value <.05 significant. Followed by Focus Group Discussion (FGD) for qualitative data, which then were analysed by thematic analysis. The last stage is integrating quantitative and qualitative data. Results: There were statistically significant differences in seven issues between the two groups. Most of the tutors in both groups had favorable opinions, except for the expert group's disagreement with the passive role of the tutor in the tutorial group. Eight positive and twelve negative perceptions were found in the FGD. Conclusion: Most tutors positively perceived their role in PBL, with the expert group having more dependable opinions and well-reasoned suggestions.